Impact of alloying elements (Co, Pt) on nickel stanogermanide formation. (15th March 2020) - Quintero, Andrea; Gergaud, Patrice; Hartmann, Jean-Michel; Reboud, Vincent; Cassan, Eric; Rodriguez, Philippe
Abstract: The impact of Pt or Co as alloying elements for Ni-based metallization of GeSn layers has been investigated. As far as the solid-state reaction is concerned, the overall phase sequence is the same for all metallizations: at low temperature, a Ni-rich phase is obtained; it is then consumed to form the low resistivity mono-stanogermanide phase. Nevertheless, the addition of an alloying element has an impact on Ni consumption, Ni-rich and mono-stanogermanide phases' formation temperatures. Moreover, the addition of Co or Pt positively impacts Sn segregation by delaying this phenomenon. Co has a weak influence on morphological and electrical properties. On the other hand, Pt improves the surface morphology by delaying the Ni(GeSn) phase agglomeration and enhancing the process window in which the sheet resistance remains low.